AI for MSMEs: Smart Solutions to Optimize Operations and Marketing - Manza, Yuke (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This research investigates the transformative potential of Artificial Intelligence (AI) for Micro, Small, and Medium Enterprises (MSMEs) in optimizing operations and marketing. Employing a mixed-methods approach—combining quantitative surveys (n=100+) and in-depth qualitative interviews (n=15-20)—the study reveals a significant positive correlation between AI adoption and enhanced operational efficiency, evidenced by average reductions of 25% in data processing time and 15% in inventory management. Furthermore, AI substantially boosts marketing effectiveness, leading to a 30% increase in audience reach and an 18% rise in sales conversion rates. Despite these clear benefits, MSMEs face considerable barriers to AI adoption, primarily financial constraints (65% of respondents) and limited digital literacy (58%). To address these challenges, the research proposes an affordable and easy-to-implement AI framework emphasizing cloud-based solutions (SaaS) and comprehensive training programs. The findings underscore AI as a crucial driver for MSME competitiveness and recommend concerted efforts from government and industry stakeholders to foster a supportive ecosystem. This study bridges the digital divide, offering evidence-based recommendations for resilient, efficient, and sustainable MSMEs in the digital era.